Identifying the effects from the quality of opposition in a Football team positioning strategy - Castellano, J.; Alvarez, D.; Figueira, B.; Coutinho, D.; Sampaio, J. (International Journal of Performance Analysis in Sport, 2013)
The present study aimed to identify the collective tactical decisions from a high-level football team, by analysing team length, width and surface area in offensive and defensive phase. The sample was composed by six competitive matches, played against stronger and weaker level opponents. Multidimensional qualitative data was obtained using a computerized match analysis system (AMISCO®). The data was analysed using non-linear signal processing tools, such as relative phase to access coordination modes between teams and approximate entropy (ApEn) to measure randomness in each time-series. The results allowed identifying higher offensive length, width and surface area frequencies when playing against weaker teams. On the other hand, higher defensive length, width and surface area frequencies were found against stronger teams. In addition, the ApEn results of surface area shown that tactical behaviour tends to be repeated during the match, both in offensive and defensive phase. The present results contributed to better understand the use of pitch space and the team strategic framework, helping coaches to improve the accuracy of strategic planning.